Molecular sieve and method for producing molecular sieve

By using the morphological modifier L in the molecular sieve synthesis process, the crystal growth is affected, and the problem of insufficient activity and selectivity of existing molecular sieve materials in catalytic hydrocarbon conversion reaction is solved, the effect of improving the surface area and external acidity is achieved, and the catalytic performance is enhanced.

CN112585092BActive Publication Date: 2025-03-04EXXONMOBIL TECHNOLOGY & ENGINEERING CO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201980054553.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-08-27
Filing Date
2019-08-20
Publication Date
2025-03-04
Estimated Expiration
2039-08-20

AI Technical Summary

Technical Problem

Existing molecular sieve materials have problems with insufficient activity and selectivity in catalyzing hydrocarbon conversion reactions, especially due to their large crystal particle size, which leads to insufficient surface area and acidity.

Method used

By adding morphological modifier L to the synthetic mixture, molecular sieve crystals with improved crystal particle size and acidity were prepared. The morphological modifier L may be a nonionic surfactant, anionic surfactant, or sugar, and combinations thereof.

Benefits of technology

The surface area and external acidity of the molecular sieve are improved, and its activity and selectivity in the catalyst is enhanced, especially in hydrocarbon conversion reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002945210450000081
    Figure BDA0002945210450000081
  • Figure BDA0002945210450000091
    Figure BDA0002945210450000091
  • Figure BDA0002945210450000271
    Figure BDA0002945210450000271
Patent Text Reader

Abstract

A method for preparing a molecular sieve is provided, wherein the method involves preparing a synthesis mixture for a molecular sieve, wherein the synthesis mixture comprises a morphology modifier L selected from a nonionic surfactant, an anionic surfactant, a sugar and a combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel method for producing crystals of molecular sieves, molecular sieves produced by the method and their use as hydrocarbon conversion catalysts. Background Art

[0002] Natural and synthetic molecular sieve materials have been proven to be used as adsorbents and have catalytic properties for various types of hydrocarbon conversion reactions in the past. Some molecular sieves are ordered porous crystalline materials with a clear crystalline structure determined by X-ray diffraction (XRD). Some molecular sieves such as MCM-41 are ordered and produce specific recognizable X-ray diffraction patterns, but are not strictly crystalline. In molecular sieve materials, there are a large number of cavities, which can be interconnected by many channels or pores. The size of these cavities and pores in specific molecular sieve materials is consistent. Because the size of these pores is suitable for receiving adsorbed molecules of a specific size, while excluding molecules of larger size, these materials have been called "molecular sieves" and are used in various industrial processes.

[0003] Such molecular sieves, both natural and synthetic, include a wide variety of crystalline silicates containing positive ions. These silicates can be described as SiO 4 and oxides of elements of Group 13 of the periodic table (e.g. AlO 4 ) three-dimensional framework. These tetrahedra are usually corner-shared via oxygen atoms, and the charge of the tetrahedra containing Group 13 elements (such as aluminum, gallium or boron) is balanced by the inclusion of cations, such as protons, alkali metals or alkaline earth metal cations.

[0004] Molecular sieves that can be used for catalysis include any naturally occurring or synthesized crystalline molecular sieves. Examples of these molecular sieves include large pore zeolites, intermediate pore diameter zeolites, and small pore zeolites. These zeolites and their isotypes are described in "Atlas of Zeolite Framework Types", eds. Ch. Baerlocher, LBM McCusker, DH Olson, Elsevier, Sixth Revised Edition, 2007, and in the online zeolite structure database http: / / www.iza-structure.org / databases / , which is incorporated herein by reference. Large pore zeolites generally have a pore size of at least about 6.5 to 7 angstroms and include LTL, MAZ, FAU, OFF, * BEA and MOR framework zeolites (IUPAC Commission of Zeolite Nomenclature). Examples of large pore zeolites include mazzite, offretite, zeolite L, zeolite Y, zeolite X, ω and β. Intermediate pore size zeolites generally have a pore size of about 4.5 angstroms to less than about 7 angstroms and include, for example, MFI, MEL, EUO, MTT, MFS, AEL, AFO, HEU, FER, MWW and TON framework zeolites (IUPAC Commission of Zeolite Nomenclature). Examples of intermediate pore size zeolites include ZSM-5, ZSM-11, ZSM-22, MCM-22, silicalite 1 and silicalite 2. Small pore size zeolites have a pore size of about 3 angstroms to less than about 5.0 angstroms and include, for example, CHA, ERI, KFI, LEV, SOD and LTA framework zeolites (IUPAC Commission of Zeolite Nomenclature). Examples of small pore zeolites include ZK-4, SAPO-34, SAPO-35, ZK-14, SAPO-42, ZK-21, ZK-22, ZK-5, ZK-20, zeolite A, chabazite, zeolite T, and ALPO-17.

[0005] Although many molecular sieves, particularly zeolites, have been established as adsorbents and catalysts commercially, there is still a need for improved molecular sieves, for example as catalysts with improved activity and / or selectivity. An aspect that has received a lot of attention recently is the crystal size (crystal size) of molecular sieves. Under other conditions being equal, the molecular sieve whose crystal size is reduced usually has an increased external surface area, which may bring increased catalytic activity by increasing the speed adsorbed on the molecular sieve crystal surface and / or by reducing the length of the diffusion path diffused into the crystal internal pores. Reducing the crystal size of the molecular sieve catalyst also can promote the reaction occurring mainly on the outer surface of the zeolite, for example, relates to the reaction of larger reactant molecules, which diffuse slowly to the internal pores due to their size.

[0006] Overview

[0007] The present invention provides a method for preparing a crystal of a molecular sieve having a framework code selected from the group consisting of MEL, MTW, TON, MTT, MRE, MWW, MFS, MOR, FAU and MSE, the method comprising the steps of:

[0008] combining at least a source of a tetravalent element X, a morphology modifier L, and water to form a synthesis mixture;

[0009] heating the synthesis mixture under crystallization conditions for a period of time ranging from about 1 hour to 100 days to form crystals of a molecular sieve, wherein the molecular sieve has a framework code selected from the group consisting of MEL, MTW, TON, MTT, MRE, MWW, MFS, MOR, FAU, and MSE; and

[0010] recovering crystals of the molecular sieve from the synthesis mixture,

[0011] wherein X=Si and the morphology modifier L is selected from nonionic surfactants, anionic surfactants, sugars and combinations thereof, and if a structure directing agent Q is present, L is different from the structure directing agent Q and is present together with the structure directing agent Q.

[0012] Optionally, the synthesis mixture further comprises a source of hydroxide ions. Optionally, the synthesis mixture further comprises a structure directing agent Q. Optionally, the synthesis mixture further comprises a source of a trivalent element Y. Optionally, the synthesis mixture further comprises a source of a pentavalent element Z. Optionally, the synthesis mixture further comprises a source of a halogen ion W. - Optionally, the synthesis mixture also contains alkali metal ions M + source and / or alkaline earth metal cations M 2+ Optionally, the synthesis mixture further comprises one or more other components.

[0013] The molecular sieve is optionally selected from ZSM-11 (MEL), ZSM-12 (MTW), ZSM-18 (MEL), ZSM-22 (TON), ZSM-23 (MTT), ZSM-48 (MRE), ZSM-57 (MFS), mordenite (MOR), cubic octahedral zeolite (FAU), hexagonal octahedral zeolite (FAU), MCM-68 (MSE) and a molecular sieve having a MWW framework code. Optionally, the molecular sieve is selected from ZSM-11, ZSM-12, ZSM-18, ZSM-22, ZSM-23, ZSM-48, MCM-49, ZSM-57, mordenite, cubic octahedral zeolite, hexagonal octahedral zeolite and MCM-68.

[0014] The inventors have found that by synthesizing the molecular sieve in the presence of a morphology modifier L, it is possible to affect crystal growth so that the crystals of the molecular sieve have improved crystal size and / or improved acidity compared to the crystals of the same molecular sieve prepared in the absence of a morphology modifier L. This enables the production of molecular sieve crystals with novel and desirable properties. The molecular sieve crystals made by the method of the present invention will be smaller than the crystals of the same molecular sieve made by the same method but in the absence of a morphology modifier L. Without wishing to be bound by theory, the inventors believe that the presence of a morphology modifier L can change the distribution of trivalent elements such as Al in the crystals and / or change the termination mode of the crystals to enhance the accessibility of trivalent elements. Compared to the crystals of the same molecular sieve made by the same method but in the absence of a morphology modifier L, the molecular sieve crystals made by the method of the present invention may have an increased surface area, especially an external surface area. Compared to the crystals of the same molecular sieve made by the same method but in the absence of a morphology modifier L, the molecular sieve crystals made by the method of the present invention may have a higher external surface acidity measured by collidine adsorption. Reduced crystal size and / or increased external surface area and / or increased external acidity can result in increased activity and / or increased selectivity of the molecular sieve when used as a component in a catalyst, such as in a hydrocarbon conversion reaction.

[0015] It has been found that the process of the present invention produces zeolite crystals having increased external surface area and / or increased surface acidity compared to the same zeolite produced under the same conditions but in the absence of morphology modifier L.

[0016] In another aspect, the present invention provides a molecular sieve having a framework code selected from the group consisting of MEL, MTW, TON, MTT, MRE, MWW, MFS, MOR, FAU and MSE, wherein the ratio of the external surface area to the internal surface area is greater than or equal to 1.1 and / or wherein the ratio of the internal acidity measured by collidine absorption to the internal acidity measured by ammonia absorption is greater than 1.1.

[0017] The present invention also provides the molecular sieve of the present invention in its as-made form. The present invention further provides the molecular sieve of the present invention in its calcined form.

[0018] The present invention further provides a catalyst comprising the molecular sieve of the present invention.

[0019] The present invention further provides a hydrocarbon conversion process comprising the step of contacting a hydrocarbon feedstock with the catalyst of the present invention.

[0020] Details

[0021] The method for making a molecular sieve according to the present invention involves preparing a synthesis mixture according to conventional techniques, except that the synthesis mixture also contains a morphology modifier L. Without being bound by any theory, it is believed that the morphology modifier L can be bound to the surface of the growth of crystallites in the synthesis mixture or otherwise interact with it, and thereby affect the morphology of the final product crystals, including size, aspect ratio (aspect ratio) and agglomeration / aggregation. Depending on the nature of the morphology modifier L and the concentration used, the product crystals may be smaller or larger than those obtained under the same conditions using the same synthesis mixture without the morphology modifier L. The morphology modifier L may also affect the distribution of any trivalent elements present and therefore may also affect the surface acidity of the molecular sieve.

[0022] Synthetic mixture

[0023] As mentioned above, the synthesis mixture can be prepared according to conventional methods. The morphology modifier L can be included in the synthesis mixture at any time during the crystallization process, but is preferably combined with the other components before nucleation or crystallization begins. Optionally, the morphology modifier L is combined with the other components of the synthesis mixture before the tetravalent element X source is added. For example, water, a hydroxide ion source (if present), a structure directing agent (if present), a trivalent element Y source (if present), a seed crystal (if present), and any other components can be combined in any order to form a mixture, and then the tetravalent element source is combined with the mixture.

[0024] In the molecular sieve of the present invention, the tetravalent element X is Si. Suitable silicon (Si) sources that can be used to prepare the synthesis mixture include silicon dioxide; colloidal suspensions of silicon dioxide, such as Precipitated silica; alkali metal silicates, such as potassium silicate and sodium silicate; tetraalkyl orthosilicates; and fumed silica, such as Aerosil and Cabosil.

[0025] The synthesis mixture optionally also contains a source of hydroxide ions, for example, the synthesis mixture may contain an alkali metal hydroxide, such as sodium hydroxide or potassium hydroxide. The hydroxide may also be present as an anion of any charged (organic) structure directing agent or modifier that may be present, or by using sodium or potassium aluminate as a source of Y, or sodium or potassium silicate as a source of X. Sodium or potassium aluminates and silicates may also be used as the alkali metal M + source.

[0026] Optionally, the trivalent element Y is selected from Al, B, Fe and Ga and mixtures thereof. Optionally, Y is selected from B, Ga or Al or mixtures thereof. Preferably, the trivalent element Y is Al. Suitable trivalent element Y sources that can be used to prepare the synthetic mixture depend on the selected element Y (e.g., boron, aluminum, iron and gallium). In embodiments where Y is boron, boron sources include boric acid, sodium tetraborate and potassium tetraborate. Optionally, the trivalent element Y is aluminum, and the aluminum source includes aluminum sulfate, aluminum nitrate, aluminum hydroxide, hydrated aluminum oxide, such as boehmite, gibbsite and pseudoboehmite, and mixtures thereof. Other aluminum sources include, but are not limited to, other water-soluble aluminum salts, alkali metal aluminate solids or liquids, aluminum alcohols such as aluminum isopropoxide, or aluminum metal, such as aluminum in the form of crumbs or powders.

[0027] As an alternative or supplement to the Si source and Al source mentioned above, a source containing both Si and Al elements may also be used as the Si and Al source. Examples of suitable sources containing both Si and Al elements include amorphous silica-alumina gel or dry silica alumina powder, silica alumina, clays such as kaolin, metakaolin and zeolites, in particular aluminosilicates such as synthetic faujasite and ultrastable faujasite, such as USY, beta or other large to medium pore zeolites. Optionally, if present, the pentavalent element Z is selected from P and As and mixtures thereof. Preferably, if present, Z is P. Suitable phosphorus sources include one or more sources selected from phosphoric acid; organic phosphates such as triethyl phosphate, tetraethyl-ammonium phosphate; aluminum phosphates; phosphates such as alkali metal phosphates, dihydrogen phosphates, hydrogen phosphates and pyrophosphates and mixtures thereof.

[0028] Optionally, the halogen ion W - , if present, is selected from chloride, bromide, fluoride and mixtures thereof. The halogen ion source may be any compound capable of releasing halogen ions in the molecular sieve synthesis mixture. Non-limiting examples of halogen ion sources include salts containing one or more halogen ions, such as metal halides, preferably wherein the metal is sodium, potassium, calcium, magnesium, strontium or barium. Suitable fluoride ions F- Sources include HF; ammonium fluoride or tetraalkylammonium fluoride, such as tetramethylammonium fluoride or tetraethylammonium fluoride; salts containing fluoride ions, such as NaF and KF; compounds of fluoride ions with elements X and Y, such as AlF 3 and SiF 6 salts; and / or compounds in which fluoride ions are present as counterions to the cationic structure directing agent Q. If the synthesis mixture does not contain a source of hydroxide ions, it preferably contains a source of fluoride ions which may also act as a mineralizer. A convenient source of halogen ions is HF.

[0029] Optionally, the synthesis mixture also contains an alkali metal cation M + and / or alkaline earth metal cations M 2+ If present, the alkali metal cation M + Preferably selected from Li + 、Na + , K + , Rb + and Cs + And mixtures thereof. Suitable Na + Sources include sodium salts such as NaCl, NaBr, NaF, or NaNO 3 ; sodium hydroxide, sodium aluminate and mixtures thereof. Suitable K + Sources include potassium hydroxide, potassium halides such as KCl, KF or NaBr, potassium nitrate and mixtures thereof. If present, the alkaline earth metal cation is preferably selected from Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ and mixtures thereof.

[0030] Structure directing agent Q is a compound known to affect the crystallization of the molecular sieve framework to promote the formation of a specific desired molecular sieve. For example, tetrapropylammonium hydroxide or bromide is commonly used to make ZSM-5. In contrast, the role of morphology modifier L is to affect crystallization to change the crystal size, surface area and / or external acidity of the molecular sieve as described above, rather than affecting the identity of the molecular sieve. If the molecular sieve is a molecular sieve that requires the use of structure directing agent Q, the synthesis mixture also contains an effective concentration of structure directing agent. In this case, morphology modifier L is different from structure directing agent Q and exists with structure directing agent Q. ZSM-12, ZSM-18, ZSM-22, ZSM-48, MCM-49, ZSM-57, mordenite and MCM-68 require the use of structure directing agents. The properties of structure directing agent Q depend on the desired framework type. Suitable structure directing agents are known to technicians. Structure directing agent Q may exist in any suitable form, for example as a salt of a halide (such as chloride or bromide), as a hydroxide or as a nitrate. The structure directing agent Q is typically an organic structure directing agent, such as an amine, such as propylamine, pyrrolidine or pyridine, or a nitrogen-containing cation, such as a quaternary ammonium cation. Optionally, the ammonium cation does not include any alkyl chain having more than 10 carbon atoms. For example, the structure directing agent Q may optionally be N,N,N-trimethyl-1-adamantanammonium hydroxide (TMAdA), where it is desired to produce a zeolite of framework type CHA. Other structure directing agents Q and related zeolites are mentioned below:

[0031] ZSM-48: hexamethonium dichloride (diquat-6-Cl2), hexamethonium dihydroxide (diquat-6-OH2), pentamethonium dichloride (diquat-5-Cl2), pentamethonium dihydroxide (diquat-5-OH2), octylamine, 1,6-diaminohexane, pyrrolidine, propylamine / tetramethylammonium hydroxide, bis(N-methylpyridyl)ethylinium, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, 1,4,8,11-tetra-aza-undecane, 1,5,9,13-tetra-aza-undecane, 1,5,8,12-tetra-aza-undecane, 1,3-diaminopropane, trimethylamine;

[0032] ZSM-18: 2,3,4,5,6,7,8,9-octahydro-2,2,5,5,8,8-hexamethyl-1 1H-benzo[1,2-c:3,4-c':5,6-c"]tripyrrolium hydroxide and chloride, butamethonium hydroxide / tetramethylammonium hydroxide;

[0033] ZSM-22: 1-aminobutane, diethylamine, ethylenediamine, 1,3-diaminopropane, 1,6-diaminohexane, 1,4,8,11-tetra-aza-undecane, 1,5,9,13-tetra-aza-undecane, 1,5,8,12-tetra-aza-undecane, N-ethylpyridinium;

[0034] ZSM-57: hexaethyl-diquat-5 dichloride, hexaethyl-diquat-5 dihydroxide;

[0035] Mordenite: tetraethylammonium hydroxide, tetraethylammonium bromide, benzyltrimethylammonium chloride, benzyltrimethylammonium hydroxide, N-ethylpyridinium bromide, N-ethylpyridinium hydroxide, trioctylamine, alkylphenol / alkylsulfonate;

[0036] MWW (including MCM-49, MCM-22, MCM-56): hexamethyleneimine, aniline, piperidine, diethyldimethylammonium hydroxide, ethyltrimethylammonium hydroxide, choline chloride, choline hydroxide, NN,N',N'-tetramethyl-1,6-diaminohexane, triethylamine, hexamethonium dihydroxide, triethanolamine;

[0037] Hexagonal faujaite (EMT): methyltriethylammonium hydroxide, tetraethylammonium hydroxide, 18-crown-6;

[0038] Cubic faujasite (FAU): 15-crown-5;

[0039] MCM-68: N,N,N',N'-tetraethylbicyclo[2.2.2]-oct-7-ene-2R,3S:5R,6S-dipyrrolium diiodide, N,N,N',N'-tetraethylbicyclo[2.2.2]-oct-7-ene-2R,3S:5R,6S-dipyrrolium dihydroxide, N,N-dimethyl-4-cyclohexylpiperazinium hydroxide, 1-butyl-1-methylpiperidinium hydroxide.

[0040] When these structure directing agents Q are present in the synthesis mixture to promote the formation of the relevant molecular sieve, they are not considered to be morphology modifiers L according to the present invention.

[0041] For aspects related to the synthesis of ZSM-48 (or other MRE framework zeolites described in the Zeolite Database maintained by the International Zeolite Association), any convenient structure directing agent suitable for use in the synthesis mixture for forming ZSM-48 can be used as the structure directing agent. One option can be to use a diquaternary alkylammonium salt having a 6-carbon atom chain between the ammonium ions (diquat-6). Another option can be to use a diquaternary alkylammonium salt having a 5-carbon atom chain between the ammonium ions (diquat-5). Both diquat-5 and diquat-6 are known to be suitable as structure directing agents for forming ZSM-48, although the resulting ZSM-48 crystals generated from diquat-5 and diquat-6 are generally different.

[0042] The synthesis mixture may have any composition suitable for preparing the desired zeolite framework. The following ranges are given as examples of desirable and preferred ranges for each pair of components in the synthesis mixture. Conveniently, XO in the synthesis mixture 2 :Y 2 O 3 The molar ratio of XO to Y may be in the range of 2 to infinity (ie, no Y), in particular 5 to 500, preferably 5 to 200. Optionally, in the synthesis mixture, the structure directing agent Q:(XO 2 +Y 2 O 3 +Z 2 O 5 ) in a molar ratio of 0.01 to 1.0, preferably 0.02 to 0.9, optionally 0.04 to 0.5. Optionally, in the synthesis mixture, H 2 O:(XO 2 +Y 2 O 3 +Z 2 O 5 ) in a molar ratio in the range of 5 to 100. Optionally, in the synthesis mixture, M + :(XO 2 +Y 2 O 3 +Z 2 O 5 ) in a molar ratio of 0 to 1.2, preferably 0 to 1.0. Optionally, in the synthesis mixture, OH - :(XO 2 +Y 2 O 3 +Z 2 O5 ) in a molar ratio of 0.05 to 1.1, preferably 0.10 to 1.0. Optionally, in the synthesis mixture, the halogen ion - :(XO 2 +Y 2 O 3 +Z 2 O 5 ) is in the range of 0 to 1, preferably 0 to 0.5. The reaction mixture may, for example, have the composition expressed in molar ratio as shown in Table 1 below:

[0043]

[0044]

[0045] Table 1: Composition ratio of synthetic mixture.

[0046] Water can be added in any amount suitable for dissolving components and preparing the desired molecular sieve. The synthesis mixture comprises an aqueous liquid phase and may also comprise some undissolved solid components and a crystalline molecular sieve. The liquid present in the synthesis mixture is substantially a single phase, typically an aqueous solution, a gel phase, a slurry, a paste or a wet powder, comprising less than 5% by weight, optionally less than 2% by weight, optionally less than 1% by weight of a water-insoluble liquid component. In particular, the liquid present in the synthesis mixture is not an emulsion or a microemulsion. The synthesis may be carried out with or without the addition of nucleation seeds. If nucleation seeds are added to the synthesis mixture, seeds are suitably present in an amount of about 0.01 to 10.0% by weight based on the synthesis mixture, such as about 0.01 to 2.0% by weight based on the synthesis mixture. Seeds may be, for example, any suitable zeolite, which may be a zeolite having the same or different framework as the zeolite to be obtained.

[0047] Morphology Modifier L

[0048] The morphology modifier L is selected from nonionic surfactants, anionic surfactants, sugars and combinations thereof. The morphology modifier can be added to the synthesis mixture at any time before crystallization is complete. Optionally, the morphology modifier L is added to the other components of the synthesis mixture before the nucleation or crystallization of the crystals begins. A mixture of two or more morphology modifiers L may also be used and such a method is within the scope of the present invention.

[0049] The morphology modifier may be a sugar. The sugar may be a monosaccharide or a disaccharide. Suitable monosaccharides include glucose, fructose and galactose, especially fructose. Suitable disaccharides include sucrose, maltose and lactose. The sugar may be a pentose. Alternatively, the sugar may be a hexose.

[0050] The morphology modifier L can be a nonionic surfactant. Optionally, the nonionic surfactant is selected from alkyl ethoxylates, alkyl propoxylates, alkylphenol ethoxylates, alkylphenol propoxylates, fatty acid ethoxylates, fatty acid propoxylates, ethoxylated amines, propoxylated amines, ethoxylated amides, propoxylated amides, block copolymers of ethylene oxide and propylene oxide, block copolymers of ethylene oxide and butylene oxide, and fatty acid esters of polyols such as glycerol and sorbitan. For example, the morphology modifier L can be PEG-lauryl ether or PEG oleyl ether.

[0051] The morphology modifier L can be an anionic surfactant. Anionic surfactants contain anionic groups, such as sulfate, sulfonate, phosphate or carboxylate groups, and an alkyl group having at least 8 carbon atoms, optionally at least 10 carbon atoms, optionally at least 12 carbon atoms, for example 14 to 30 carbon atoms. Optionally, the anionic surfactant is an alkyl sulfate, alkyl sulfonate, alkyl phosphate or alkyl carboxylate. Optionally, the anionic surfactant is an alkyl sulfate, such as sodium lauryl sulfate.

[0052] The molar ratio L:X in the synthesis mixture is optionally in the range of 0.0001 to 0.10, optionally 0.0001 to 0.08, optionally 0.0001 to 0.05, optionally 0.0001 to 0.03, optionally 0.001 to 0.025. At lower ratios, the concentration of the morphology modifier L may not be sufficient to cause a significant change in the crystal morphology, while at higher ratios, the concentration of the morphology modifier may be so great as to inhibit crystallization, thereby significantly reducing the crystallization rate, or resulting in the formation of another molecular sieve framework instead of the desired framework.

[0053] The morphology modifier L is optionally present in the synthesis mixture in a concentration of 0.01 to 10 wt %, optionally 0.1 to 5 wt %, optionally 0.2 to 3 wt %, preferably 0.5 to 2 wt %, based on the weight of the synthesis mixture.

[0054] Crystallization and recovery

[0055] The reaction mixture may be prepared in a suitable reactor vessel, such as a polypropylene tank or Bottles, acid digestion containers, Crystallization is carried out in a tumbler-lined or stainless steel autoclave, plough shear mixers or reactor under static or stirring conditions. Crystallization is generally carried out at a temperature of about 80° C. to about 250° C., optionally 100° C. to about 200° C., optionally about 150° C. to about 170° C., for a time sufficient for crystallization to occur at the temperature used, for example, about 1 day to about 100 days, particularly 1 to 50 days, for example about 2 days to about 40 days. Thereafter, the synthesized crystals are separated from the mother liquor by any convenient method, such as filtration or centrifugation and recovered. The crystals are then dried, for example, under atmospheric conditions, washed with a low boiling point solvent, such as acetone, methanol, ethanol or propanol, microwave conditions, or dried in an oven at a temperature of up to 150° C.

[0056] Calcination

[0057] The process optionally comprises the step of calcining the crystals recovered in step c) to produce a calcined form of the molecular sieve. The calcination conditions are selected to at least partially remove any remaining organic residues normally trapped in the pores of the molecular sieve in its "as-made" form, such as remaining morphology modifier L and / or any structure directing agent Q (if used).

[0058] The calcining step typically involves heating the zeolite at a temperature of at least about 200° C., preferably at least about 300° C., more preferably at least about 370° C., for at least 1 minute and typically not longer than 20 hours. Although pressures less than one atmosphere may be used for the heat treatment, atmospheric pressure is generally desirable for reasons of convenience. The heat treatment may be conducted at a temperature of up to about 1100° C. For example, the heat treatment may be conducted in the presence of an oxygen-containing gas (e.g., in air) at a temperature of 400 to 600° C., e.g., 500 to 550° C.

[0059] The molecular sieve may also be subjected to an ion exchange treatment, such as aqueous ammonium nitrate, to remove the remaining alkali metal cations and / or alkaline earth metal cations and replace them with protons, thereby producing the acid form of the molecular sieve. To the desired extent, the original cations of the as-synthesized material, such as alkali metal cations, may be replaced by other cations by ion exchange. Preferred alternative cations may include metal ions, hydrogen ions, hydrogen precursors, such as ammonium ions and mixtures thereof. Particularly preferred cations may be those that regulate the catalytic activity of certain hydrocarbon conversion reactions. These may include hydrogen, rare earth metals and metals of Groups IIA, IIIA, IVA, VA, IB, IIB, IIIB, IVB, VB, VIB, VIIB and VIII of the periodic table. The ion exchange step may be performed after the original molecular sieve is dried. The ion exchange step may be performed before or after the calcination step.

[0060] The molecular sieve may also be subjected to other treatments, such as steam treatment and / or washing with a solvent. Such treatments are well known to the skilled person and are carried out in order to change the properties of the molecular sieve as desired.

[0061] Molecular sieve

[0062] The molecular sieve of the present invention and the molecular sieve made by the method of the present invention are molecular sieves with a framework code selected from MEL, MTW, TON, MTT, MRE, MWW, MFS, MOR, FAU and MSE. Optionally, the molecular sieve is a zeolite selected from ZSM-11, ZSM-12, ZSM-18, ZSM-22, ZSM-23, ZSM-48, MCM-49, ZSM-57, mordenite, cubic octahedral zeolite, hexagonal octahedral zeolite and MCM-68. Details of framework type and pore dimension are given in Table 2 below.

[0063] Molecular sieve Skeleton Type Dimensionality ZSM-11 MEL 2 ZSM-12 MTW 1 ZSM-18 MEI 1 ZSM-22 TON 1 ZSM-23 MTT 1 ZSM-48 MRE 1 MCM-49 MWW 2 ZSM-57 MFS 2 Mordenite MOR 2 Cubic octahedral zeolite FAU 3 Hexagonal zeolite EMT 3 MCM-68 MSE 3

[0064] Table 2: Molecular sieve framework types and pore dimensions

[0065] Optionally, the molecular sieve is selected from ZSM-12, ZSM-18, ZSM-22, ZSM-48, MCM-49, ZSM-57, cuboshite and hexagonal zeolite. Optionally, the molecular sieve is selected from ZSM-12, ZSM-18 and ZSM-48. Optionally, the molecular sieve is selected from MCM-49, ZSM-57 and mordenite. Optionally, the molecular sieve is selected from cuboshite, hexagonal zeolite and MCM-68. ZSM-48 and MCM-49 are particularly preferred molecular sieves.

[0066] ZSM-50, zeolite beta, ZSM-10, chabazite and zeolite A are all additional molecular sieves that can be produced according to the process of the present invention, so the molecular sieve of the present invention can be selected from ZSM-11, ZSM-12, ZSM-18, ZSM-22, ZSM-23, ZSM-48, MCM-49, ZSM-57, mordenite, cubohedrite, hexagonalhedite and MCM-68, ZSM-50, zeolite beta, ZSM-10, chabazite and zeolite A in another embodiment.

[0067] The molecular sieve prepared by the method of the present invention may have an increased surface area compared to the same molecular sieve prepared in the absence of the morphology modifier L. Optionally, the surface area of ​​the molecular sieve prepared by the method of the present invention is at least 1.1 times, optionally at least 1.2 times, the surface area of ​​the same molecular sieve prepared in the absence of the morphology modifier L.

[0068] The molecular sieve prepared by the method of the present invention may have an increased external acidity as measured by collidine absorption compared to the same molecular sieve prepared in the absence of morphology modifier L. Optionally, the external acidity of the molecular sieve prepared by the method of the present invention is at least 1.1 times, optionally at least 1.2 times, the external acidity of the same molecular sieve prepared in the absence of morphology modifier L.

[0069] Alternatively, the molecular sieve produced by the process of the present invention has a reduced external surface area and / or reduced external acidity compared to the same molecular sieve produced in the absence of the morphology modifier L.

[0070] By selecting an appropriate morphology modifier L and an appropriate concentration of the morphology modifier, one can prepare molecular sieves having a range of external surface areas, external acidities and / or crystal sizes.

[0071] The molecular sieves of the present invention preferably have a ratio of external surface area to internal surface area greater than 1.20 and / or have a ratio of external acidity as measured by collidine absorption to internal acidity as measured by ammonia absorption greater than 1.50.

[0072] In some aspects, the molecular sieves made by the methods described herein may form agglomerates of small crystals that may have a crystal size of 0.01 to 1 μm in a calcined form or in an original synthesis form. These small crystals may be desirable because they generally bring higher activity. Smaller crystals may mean larger surface area, which may bring higher activity of the catalyst.

[0073] Optionally, the zeolite contains Si and Al and has a SiO ratio greater than 2:1, optionally greater than 5:1, optionally greater than 10:1, optionally greater than 30:1, optionally greater than 100:1, and optionally greater than 150:1. 2 :Al 2 O 3 Molar ratio. SiO 2 :Al 2 O 3 The molar ratio is optionally less than 500, optionally less than 300, or optionally less than 200. Although the presence of aluminum within the framework structure does contribute acid sites to the catalyst, it is also associated with a decrease in the thermal stability of the zeolite. Many industrial organic feedstock conversion processes require the use of zeolites having SiO2 ratios greater than 6:1 or even greater than 10:1. 2 :Al 2 O 3 The molar ratio of the zeolite support is carried out at this temperature.

[0074] The molecular sieve optionally has a crystallinity of at least 80%, optionally at least 90%, preferably at least 95%, and most preferably at least 98%. In one embodiment, the molecular sieve is a substantially pure crystalline material. The crystallinity can be calculated by X-ray diffraction (XRD).

[0075] In one embodiment, the molecular sieve is in its as-prepared form and optionally contains a structure directing agent Q within its pores.

[0076] In another embodiment, the molecular sieve does not contain a structure directing agent Q. For example, the molecular sieve may be a molecular sieve synthesized without any structure directing agent Q. The molecular sieve may be in a calcined form. The molecular sieve crystal may be an "as-synthesized" crystal still containing an organic template, or the crystal may be a calcined crystal, such as a K-form molecular sieve crystal or a Na-form molecular sieve crystal, or the crystal may be a calcined and ion-exchanged crystal, such as an H-form molecular sieve crystal.

[0077] The molecular sieve of the present invention in its calcined acid form preferably has an external acidity of at least 1.10 times, more preferably at least 1.30 times, and in some cases at least 1.50 times, the external acidity of a molecular sieve made using the same method except that the synthesis mixture does not contain any morphology modifier L. The external acidity can be measured by collidine adsorption.

[0078] The molecular sieve of the present invention in its calcined acid form may have an external surface area at least 1.10 times, more preferably at least 1.20 times, and in some cases 1.30 times, greater than the external surface area of ​​a molecular sieve made using the same method except that the synthesis mixture does not contain any morphology modifier L. The external surface area may be measured by BET.

[0079] The molecular sieves of the invention, in their calcined form, preferably have a ratio of external surface area to internal surface area greater than 1.20 and / or a ratio of external acidity as measured by collidine absorption to internal acidity as measured by ammonia absorption greater than 1.50.

[0080] The molecular sieve of the present invention or the molecular sieve made by the method of the present invention can be used as an adsorbent or as a catalyst to catalyze a wide variety of organic compound conversion processes, including many processes currently important commercially / industrially. Examples of preferred chemical conversion processes that can be effectively catalyzed by the zeolite of the present invention or the zeolite made by the method of the present invention (alone or in combination with one or more other catalytically active substances (including other crystalline catalysts)) include those that require catalysts with acid activity or hydrogenation activity. Examples of organic conversion processes that can be catalyzed by the zeolite of the present invention or the zeolite made by the method of the present invention include cracking, hydrocracking, isomerization, polymerization, reforming, hydrogenation, dehydrogenation, dewaxing, hydrodewaxing, adsorption, alkylation, transalkylation, dealkylation, hydrogenation ring opening, disproportionation, oligomerization, dehydrogenation cyclization and combinations thereof. The conversion of hydrocarbon feed can be carried out in any convenient mode, for example in a fluidized bed, an ebullating bed, a moving bed or a fixed bed reactor, depending on the type of the desired process.

[0081] Once the molecular sieve is synthesized, it can be formulated into a catalyst composition by combining it with other materials such as binders and / or matrix materials that provide additional hardness or catalytic activity to the finished catalyst. These other materials can be inert or catalytically active materials.

[0082] In particular, it may be desirable to combine the molecular sieve of the present invention or the molecular sieve made by the method of the present invention with another material that tolerates the temperature and other conditions used in the organic conversion process. Such materials include synthetic or naturally occurring zeolites, and inorganic materials, such as clays, silica and / or metal oxides, such as aluminum oxide, yttrium oxide, zirconium oxide, gallium oxide, zinc oxide and mixtures thereof. The metal oxide may be naturally occurring, or in the form of a gelatinous precipitate or gel containing a mixture of silica and metal oxides. Available natural clays include montmorillonite and kaolin families, which include subbentonites, and kaolins commonly referred to as Dixie, McNamee, Georgia and Florida clays, or other ones in which the main mineral components are halloysite, kaolinite, dickite, nacrite or anauxite. Such clays may be used in the original state of original mining or after calcination, acid treatment or chemical modification. These binder materials are resistant to the temperatures and other conditions present in various hydrocarbon conversion processes, such as mechanical grinding. Therefore, the molecular sieve of the present invention or the molecular sieve made by the method of the present invention can be used in the form of an extrudate containing a binder. They are usually bonded by forming pellets, spheres or extrudates. The extrudate is usually formed by extruding the molecular sieve (optionally in the presence of a binder) and drying and calcining the resulting extrudate. Further treatments such as steam treatment, addition of catalytic metals and / or ion exchange can be performed as needed. The molecular sieve can be optionally used with a 200 m 2 / g, optional at least 300m 2 / g of surface area of ​​adhesive bonding.

[0083] Binders may suitably act as diluents to control the amount of conversion in a given process so as to obtain the product in an economical and orderly manner without the use of other means of controlling the reaction rate. These materials may be incorporated into natural clays (e.g., bentonite and kaolin) to improve the crush strength of the catalyst under commercial operating conditions.

[0084] In addition to the above materials, the molecular sieve of the present invention can also be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia and silica-magnesia-zirconia.

[0085] The relative proportions of the molecular sieve and the inorganic oxide matrix can vary widely, with the molecular sieve content ranging from about 1 to about 100 weight percent, more typically, especially when the composite is prepared in the form of an extrudate, from about 2 to about 95, optionally from about 20 to about 90 weight percent of the composite.

[0086] Additional Implementation

[0087] Additionally or alternatively, the present disclosure may include one or more of the following embodiments.

[0088] Embodiment 1. A method for preparing crystals of a molecular sieve having a framework code selected from the group consisting of MEL, MTW, TON, MTT, MRE, MWW, MFS, MOR, FAU and MSE, the method comprising the steps of:

[0089] a. Combining a tetravalent element X source, a morphology modifier L, water, an optional hydroxide ion source, an optional structure directing agent Q, an optional trivalent element Y source, an optional pentavalent element Z source, and an optional halogen ion W - source, optionally alkali metal ions M + source and / or alkaline earth metal cations M 2+ a source and optionally one or more other components to form a synthesis mixture;

[0090] b. heating the synthesis mixture under crystallization conditions for a period of time ranging from about 1 hour to 100 days to form crystals of the molecular sieve; and

[0091] c. recovering crystals of the molecular sieve from the synthesis mixture,

[0092] wherein X=Si and the morphology modifier L is selected from the group consisting of nonionic surfactants, anionic surfactants, sugars, and combinations thereof, and if a structure directing agent Q is present, L is different from the structure directing agent Q and is present together with the structure directing agent Q.

[0093] Embodiment 2. The method of Embodiment 1, wherein the molar ratio L:X in the synthesis mixture is in the range of 0.001 to 0.03.

[0094] Embodiment 3. The method of Embodiment 1 or 2, wherein Y is present in the synthesis mixture and is Al, and XO 2 :Y 2 O 3 The ratio is in the range of 5 to 500.

[0095] Embodiment 4. The method of any one of Embodiments 1 to 3, wherein the ratio Q: (X 2 +Y 2 O 3 +Z 2 O 5) is in the range of 0.01 to 1.0.

[0096] Embodiment 5. The method of any one of embodiments 1 to 4, wherein the morphology-modifying agent L is a monosaccharide.

[0097] Embodiment 6. The method of any one of Embodiments 1 to 4, wherein the morphology modifier L is an anionic surfactant.

[0098] Embodiment 7. The method of Embodiment 6, wherein the anionic surfactant is an alkyl sulfate.

[0099] Embodiment 8. The method of Embodiment 7, wherein the alkyl sulfate is a C8 to C30 alkyl sulfate.

[0100] Embodiment 9. The method of any one of Embodiments 1 to 4, wherein the morphology modifier L is a nonionic surfactant.

[0101] Embodiment 10. The method of Embodiment 9, wherein the nonionic surfactant is a block copolymer comprising one or more blocks derived from ethylene oxide and one or more blocks derived from propylene oxide.

[0102] Embodiment 11. The method of any of Embodiments 1 to 10, wherein the synthesis mixture is substantially free of water-insoluble liquid components.

[0103] Embodiment 12. The method of any one of Embodiments 1 to 11, comprising the step of calcining the crystals recovered in step c) to produce a calcined form of the molecular sieve.

[0104] Embodiment 13. The method of any one of Embodiments 1 to 12, wherein the molecular sieve is a zeolite selected from the group consisting of ZSM-11, ZSM-12, ZSM-18, ZSM-22, ZSM-23, ZSM-48, MCM-49, ZSM-57, mordenite, cuboctahedrite, hexagonal zeolite and MCM-68.

[0105] Embodiment 14. A molecular sieve having a framework code selected from the group consisting of MEL, MTW, TON, MTT, MRE, MWW, MFS, MOR, FAU and MSE, wherein the ratio of external surface area to internal surface area is greater than 1.2 and / or wherein the ratio of external acidity measured by collidine absorption to internal acidity measured by ammonia absorption is greater than 1.5.

[0106] Embodiment 15. The molecular sieve according to embodiment 14, which is a zeolite selected from the group consisting of ZSM-11, ZSM-12, ZSM-18, ZSM-22, ZSM-23, ZSM-48, MCM-49, ZSM-57, mordenite, cuboctahedite, hexagonal zeolite and MCM-68.

[0107] Embodiment 16. The molecular sieve according to Embodiment 14 or 15 prepared according to the method of any one of Embodiments 1 to 12.

[0108] Embodiment 17. A catalyst comprising the molecular sieve of any one of Embodiments 14 to 16 and optionally comprising a binder.

[0109] Embodiment 18. A hydrocarbon conversion method comprising the step of contacting a hydrocarbon feedstock with the catalyst described in Embodiment 17.

[0110] Embodiment 19. The hydrocarbon conversion process described in Embodiment 18, which is a dewaxing process or an aromatic compound alkylation process. Example

[0111] The synthesis of ZSM-48 was carried out according to the following procedure using hexamethyldiammonium dichloride (HMDC) as a structure directing agent and different morphology modifiers.

[0112] Example 1 (Comparative). ZSM-48 reference, no morphology modifier, morphology modifier / SiO 2 = 0.0, the morphology modifier is present at 0 wt% of the total mixture

[0113] 1.26 g of 25% hexamethonium chloride (HMDC) was diluted in 14.8 g of water. Stir to ensure a homogeneous solution. 0.62 g of sodium aluminate solution (7.8% Na 2 O, 10.0% Al 2 O 3 , 82.2% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.73 grams of colloidal beta seeds (17.2 wt% seeds) were added to the aluminate mixture. 3.95 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0114] SiO 2 / Al 2 O 3 =100.0

[0115] OH- / SiO 2 =0.175

[0116] HMDC / SiO 2 =0.019

[0117] Modifier / SiO 2 =0.000

[0118] H 2 O / SiO 2 =18.7

[0119] ~5100ppm seed

[0120] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0121] Transmission electron microscopy (TEM) revealed that the crystals have a length typically between 30 and 50 nm and a width between 10 and 15 nm, with a length:width aspect ratio of 3 to 5.

[0122] Example 2. ZSM-48, Brij L4 morphology modifier, morphology modifier / SiO 2 = 0.017, 1.5% by weight of the total mixture

[0123] 1.24 g of 25% hexamethonium dichloride (HMDC) was diluted in 13.0 g of water. Stir to ensure a homogeneous solution. 0.59 g of sodium aluminate solution (7.5% Na 2 O, 10.2% Al 2 O 3 , 82.3% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.75 grams of colloidal beta seeds (16.7 wt % seeds) were added to the aluminate mixture. 1.96 grams of 19.2 wt % Brij L4 solution (polyethylene glycol lauryl ether as a non-ionic surfactant morphology modifier) ​​was added and the mixture was stirred to dissolve the zeolite growth modifier. 3.89 grams of Ultrasil VN3PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0124] SiO 2 / Al2 O 3 =100.0

[0125] OH - / SiO 2 =0.175

[0126] HMDC / SiO 2 =0.019

[0127] Modifier / SiO 2 =0.017

[0128] H 2 O / SiO 2 =18.7

[0129] ~5200ppm seed

[0130] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0131] Example 3. ZSM-48, Brij 93 morphology modifier, morphology modifier / SiO 2 =0.018, 1.5 wt% of the total mixture

[0132] 1.27 g of 25% hexamethonium chloride (HMDC) was diluted in 12.9 g of water. Stir to ensure a homogeneous solution. 0.59 g of sodium aluminate solution (7.5% Na 2 O, 10.2% Al 2 O 3 , 82.3% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.75 grams of colloidal beta seeds (16.7 wt % seeds) were added to the aluminate mixture. 2.02 grams of 18.54 wt % Brij 93 solution (polyethylene glycol oleyl ether as a nonionic surfactant morphology modifier) ​​was added and the mixture was stirred to dissolve the zeolite growth modifier. 3.89 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0133] SiO 2 / Al 2 O 3=100.0

[0134] OH - / SiO 2 =0.175

[0135] HMDC / SiO 2 =0.019

[0136] Modifier / SiO 2 =0.018

[0137] H 2 O / SiO 2 =18.7

[0138] ~5200ppm seed

[0139] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0140] Example 4. ZSM-48, sodium octyl sulfate morphology modifier, morphology modifier / SiO 2 = 0.027, 1.5% by weight of the total mixture

[0141] 1.27 g of 25% hexamethonium chloride (HMDC) was diluted in 13.0 g of water. Stir to ensure a homogeneous solution. 0.60 g of sodium aluminate solution (7.5% Na 2 O, 10.2% Al 2 O 3 , 82.3% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.75 grams of colloidal beta seeds (16.7 wt % seeds) were added to the aluminate mixture. 1.86 grams of 20 wt % sodium octyl sulfate solution was added and the mixture was stirred to dissolve the zeolite growth modifier. 3.89 grams of Ultrasil VN3PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0142] SiO 2 / Al 2 O 3 =100.0

[0143] OH - / SiO2 =0.175

[0144] HMDC / SiO 2 =0.019

[0145] Modifier / SiO 2 =0.027

[0146] H 2 O / SiO 2 =18.7

[0147] ~5200ppm seed

[0148] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0149] Example 5 (Comparative) ZSM-48, 1,2-hexanediol comparative modifier, comparative modifier / SiO 2 =0.053, 1.5 wt% of the total mixture

[0150] 1.27 g of 25% hexamethonium chloride (HMDC) was diluted in 13.1 g of water. Stir to ensure a homogeneous solution. 0.60 g of sodium aluminate solution (7.5% Na 2 O, 10.2% Al 2 O 3 , 82.3% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.75 grams of colloidal beta seeds (16.7 wt % seeds) were added to the aluminate mixture. 1.86 grams of 20.1 wt % 1,2-hexanediol solution was added and the mixture was stirred to dissolve the zeolite growth modifier. 3.89 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0151] SiO 2 / Al 2 O 3 =100.0

[0152] OH - / SiO 2 =0.175

[0153] HMDC / SiO 2 =0.019

[0154] Modifier / SiO 2 =0.053

[0155] H 2 O / SiO 2 =18.7

[0156] ~5200ppm seed

[0157] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0158] Example 6. ZSM-48, sodium dodecyl sulfate morphology modifier, morphology modifier / SiO 2 = 0.029, 2.0 wt% of the total mixture

[0159] 1.24 g of 25% hexamethonium chloride (HMDC) was diluted in 12.5 g of water. Stir to ensure a homogeneous solution. 0.61 g of sodium aluminate solution (7.8% Na 2 O, 10.0% Al 2 O 3 , 82.2% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.73 grams of colloidal beta seeds (17.2 wt% seeds) were added to the aluminate mixture. 2.5 grams of 20 wt% sodium dodecyl sulfate solution (anionic surfactant morphology modifier) ​​was added and the mixture was stirred to dissolve the morphology modifier. 3.90 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0160] SiO 2 / Al 2 O 3 =100.2

[0161] OH - / SiO 2 =0.174

[0162] HMDC / SiO 2 =0.019

[0163] Modifier / SiO 2 =0.029

[0164] H 2 O / SiO 2 =18.6

[0165] ~5100ppm seed

[0166] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0167] Example 7. ZSM-48, sodium dodecyl sulfate morphology modifier, morphology modifier / SiO 2 = 0.073, 5.0% by weight of the total mixture

[0168] 1.2 g of 25% hexamethonium chloride (HMDC) was diluted in 9.1 g of water. Stir to ensure a homogeneous solution. 0.59 g of sodium aluminate solution (7.8% Na 2 O, 10.0% Al 2 O 3 , 82.2% water) was added to the structure directing solution. Stir to homogenize the solution. 3.4 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.73 grams of colloidal beta seeds (17.2 wt% seeds) were added to the aluminate mixture. 6.3 grams of 20 wt% sodium dodecyl sulfate solution (anionic surfactant morphology modifier) ​​was added and the mixture was stirred to dissolve the morphology modifier. 3.78 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0169] SiO 2 / Al 2 O 3 =100.9

[0170] OH - / SiO 2 =0.174

[0171] HMDC / SiO 2 =0.019

[0172] Modifier / SiO 2 =0.073

[0173] H 2 O / SiO 2 =18.6

[0174] ~5100ppm seed

[0175] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0176] Example 8. ZSM-48 lithium dodecyl sulfate morphology modifier, morphology modifier / SiO 2 =0.023, 1.5 wt% of the total mixture

[0177] 1.24 g of 25% hexamethonium dichloride (HMDC) was diluted in 13.1 g of water. Stir to ensure a homogeneous solution. 0.61 g of sodium aluminate solution (7.8% Na2O, 10.0% Al 2 O 3 , 82.2% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.73 grams of colloidal beta seeds (17.2 wt% seeds) were added to the aluminate mixture. 1.86 grams of 20 wt% lithium dodecyl sulfate solution (anionic surfactant morphology modifier) ​​was added and the mixture was stirred to dissolve the morphology modifier. 3.89 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0178] SiO 2 / Al 2 O 3 =100.0

[0179] OH- / SiO 2 =0.175

[0180] HMDC / SiO 2 =0.019

[0181] Modifier / SiO 2 =0.023

[0182] H 2 O / SiO 2 =18.7

[0183] ~5100ppm seed

[0184] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0185] Transmission electron microscopy (TEM) revealed that the crystals have a length of typically 30 to 60 nm and a width of approximately 30 nm, with a length:width aspect ratio of 1 to 2.

[0186] Example 9. ZSM-48 Pluronic EO-PO-EO Morphology Modifier, Morphology Modifier / SiO 2 = 0.0007, 1.0 wt% of the total mixture

[0187] 1.25 g of 25% hexamethonium dichloride (HMDC) was diluted in 13.7 g of water. Stir to ensure a homogeneous solution. 0.61 g of sodium aluminate solution (7.8% Na2O, 10.0% Al 2 O 3 , 82.2% water) was added to the structure directing solution. Stir to homogenize the solution. 3.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.73 grams of colloidal beta seeds (17.2 wt% seeds) were added to the aluminate mixture. 1.24 grams of 20 wt% Pluronic EO-PO-EO triblock copolymer solution (non-ionic surfactant morphology modifier) ​​was added and the mixture was stirred to dissolve the morphology modifier. 3.91 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0188] SiO 2 / Al 2 O 3 =100.0

[0189] OH- / SiO 2 =0.175

[0190] HMDC / SiO 2 =0.019

[0191] Modifier / SiO 2 =0.0007

[0192] H 2 O / SiO 2 =18.7

[0193] ~5100ppm seed

[0194] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0195] The following synthesis of MCM-49 was carried out according to the following procedure using hexamethyleneimine (HMI) as the structure directing agent.

[0196] Example 10. MCM-49 reference, no morphology modifier, morphology modifier / SiO 2 = 0.000, 0% by weight of the total mixture

[0197] 3.54 g of 40 wt% aluminum sulfate octahydrate solution was diluted in 12.0 g of water. 4.1 g of 20% NaOH solution was added to the aluminum sulfate solution. Stir to homogenize the mixture. 3.46 g of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the sodium aluminate solution. The mixture was stirred until the slurry looked uniform. 1.86 grams of hexamethyleneimine (HMI) was added to the slurry. The mixture was stirred for 10 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0198] SiO 2 / Al 2 O 3 =25.0

[0199] OH- / SiO 2 =0.390

[0200] HMI / SiO 2 =0.350

[0201] Modifier / SiO 2 =0.000

[0202] H 2 O / SiO 2 =18.5

[0203] The autoclave was sealed and the mixture was continued to be stirred at 360 rpm with a U-type stirrer. The mixture was heated to 143° C. (20° C. / hr. ramp rate) and maintained for 5 days. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in a furnace at 120° C. X-ray diffraction showed that the powder was of MCM-49 / MCM-22 structure type.

[0204] Example 11. MCM-49 sodium dodecyl sulfate morphology modifier, morphology modifier / SiO 2 =0.016, 1% by weight of the total mixture

[0205] 3.54 g of 40 wt% aluminum sulfate octahydrate solution was diluted in 12.0 g of water. 4.1 g of 20% NaOH solution was added to the aluminum sulfate solution. Stir to homogenize the mixture. 3.46 g of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the sodium aluminate solution. The mixture was stirred until the slurry looked uniform. 1.85 grams of hexamethyleneimine (HMI) was added to the slurry. 1.27 grams of a 20 wt % sodium dodecyl sulfate solution (anionic surfactant morphology modifier) ​​was added to the slurry. The mixture was stirred for 10 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0206] SiO 2 / Al 2 O 3 =25.0

[0207] OH- / SiO 2 =0.390

[0208] HMI / SiO 2 =0.350

[0209] Modifier / SiO 2 =0.016

[0210] H 2 O / SiO 2 =19.6

[0211] The autoclave was sealed and the mixture was continued to be stirred at 360 rpm with a U-type stirrer. The mixture was heated to 143° C. (20° C. / hr. ramp rate) and maintained for 5 days. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in a furnace at 120° C. X-ray diffraction showed that the powder was of MCM-49 / MCM-22 structure type.

[0212] Example 12. ZSM-48 fructose morphology modifier, modifier / SiO 2=0.020, 1.0 wt% of the total mixture

[0213] Dilute 1.39 g of 56% hexamethonium chloride (HMDC) in 14.4 g of water. Stir to ensure a homogeneous solution. Add 1.42 g of sodium aluminate solution (20% NaOH, 7.8% Al(OH) 3 , 72.2% water) was added to the structure directing solution. Stir to homogenize the solution. 2.6 grams of 10% NaOH solution was added to the HMDC / aluminate solution. Stir to homogenize the mixture. 0.03 grams of ZSM-48 seeds were added to the aluminate mixture. 0.63 grams of 39.7% fructose solution was added and stirred to homogenize the mixture. 4.62 grams of Ultrasil VN3 PM modified precipitated silica (92.4% SiO 2 ) was added to the mixture. The mixture was stirred for 15 minutes to prepare a uniform slurry. The approximate molar gel composition of the mixture was as follows:

[0214] SiO 2 / Al 2 O 3 =99.9

[0215] OH- / SiO 2 =0.190

[0216] HMDC / SiO 2 =0.040

[0217] Modifier / SiO 2 =0.020

[0218] H 2 O / SiO 2 =14.9

[0219] ~1000ppm seed

[0220] The autoclave was sealed and the mixture was continued to be stirred at 300 rpm with a U-type stirrer. The mixture was heated to 160°C (20°C / hr. ramp rate) and maintained for 28 hours. The solid was separated by vacuum filtration and washed with 3 volumes of water. The material was dried in an oven at 120°C. X-ray diffraction indicated that the powder was ZSM-48.

[0221] Post-synthesis processing and measurement

[0222] Samples of the molecular sieves prepared according to Examples 1 to 12 above were subjected to the following treatments.

[0223] After the crystallization is completed and the material is determined by XRD, the crystals are 4 NO 3Ion exchanged twice, washed with water and dried in an oven at 120° C. The ammonium form of the powder was then calcined in air at 550° C. for 2 hours to produce the acid form of the zeolite crystals.

[0224] The acid form of the crystals was then characterized using collidine adsorption to assess the acidity of the catalyst. The surface area (total surface area and external surface area) and pore volume of the crystals were determined using the nitrogen BET technique. These data for the reference material and each modified material of the present invention were collected, and the ratio of the external surface area of ​​each embodiment of the present invention to the reference embodiment of the same zeolite and the ratio of collidine absorption are shown in Table 3 to confirm the changes in the acidity and external surface area of ​​the modified crystals caused by the presence of the morphology modifier in the synthesis mixture.

[0225] BET analysis was performed as described in SJ Gregg, KSW Sing, "Adsorption, Surface Area and Porosity", Istted., Academic Press, NY (1967), pp. 30-31. Ammonia and collidine absorption experiments were performed as described in J. Phys. Chem. B, 2002, 106 (2), pp. 395-400 (note that the equipment was slightly different in some cases, but in all cases the measurements were performed on a thermogravimetric balance).

[0226]

[0227] Table 3: Collidine absorption and external surface area results for Examples 1 to 12

[0228] The results in Table 3 show that when 1,2-hexanediol (which is not a morphology modifier as described herein) is used, no effect is seen on collidine absorption or external surface area, which are the same as the reference ZSM-48 of Comparative Example 1.

[0229] For Examples 2-4, 9, 11 and 12 of the present invention, the presence of a morphology modifier has a significant effect on the collidine absorption and / or external surface area compared to a synthesis of a reference material in the absence of the morphology modifier. In Examples 6 and 7, the recorded collidine absorption and external surface area values ​​are lower than the reference synthesis of the same zeolite in the absence of the morphology modifier, but are within 10% and therefore may be attributed to experimental error. For Example 8, the collidine absorption and external surface area results are lower than the reference material. In this case, the TEM results indicate that the aspect ratio of the crystals made in the presence of lithium dodecyl sulfate as a morphology modifier is significantly reduced compared to the reference ZSM-48, which is mainly due to the increase in the width of the crystals compared to the reference material. In ZSM-48, the one-dimensional channels in the framework run longitudinally through the crystal, so the increase in the width of the crystal compared to the length may make these channels more available to the introduced reactant molecules.

Claims

1. Use of anionic surfactant as morphology modifier L in a method for preparing crystals of a molecular sieve having a framework code selected from MRE and MWW, the method for preparing the crystals of the molecular sieve comprising the steps of: a. combining at least a source of a tetravalent element X, a morphology modifier L and water to form a synthesis mixture, wherein the morphology modifier L is contained in the synthesis mixture before nucleation or crystallization begins; b. heating the synthesis mixture under crystallization conditions for a period of time ranging from 1 hour to 100 days to form crystals of the molecular sieve; and c. recovering crystals of the molecular sieve from the synthesis mixture, wherein X = Si, and if a structure directing agent Q is present, L is different from the structure directing agent Q and is present together with the structure directing agent Q, The morphology modifier L is an anionic surfactant, Wherein when the molecular sieve has a framework code MRE, the anionic surfactant is octyl sulfate, and when the molecular sieve has a framework code MWW, the anionic surfactant is dodecyl sulfate, wherein the molecular sieve with a framework code MRE is ZSM-48 zeolite, and the molecular sieve with a framework code MWW is MCM-49 zeolite, and The crystals of the molecular sieve have improved crystal size, external surface area and / or external acidity compared to crystals of the same molecular sieve made by the same process but in the absence of the morphology modifier L.

2. The method as claimed in claim 1, wherein in step a) a source selected from the group consisting of a hydroxide ion source, a structure directing agent Q, a trivalent element Y source, a pentavalent element Z source, a halogen ion W-source, an alkali metal ion M + source and / or alkaline earth metal cations M 2+ One or more additional components of the source are combined into the synthesis mixture.

3. The method according to claim 1, wherein the molar ratio L:X in the synthesis mixture is in the range of 0.001 to 0.

03.

4. The method as claimed in claim 1, wherein a source of a trivalent element Y is present in the synthesis mixture and Y is Al, and the molar ratio of XO2:Y2O3 is in the range of 5 to 500.

5. The use as claimed in claim 2, wherein the molar ratio Q: (XO2+Y2O3+Z2O5) is in the range of 0.01 to 1.

0.

6. The method as claimed in claim 1, wherein the synthesis mixture does not contain water-insoluble liquid components.

7. The use as claimed in claim 1, comprising the step of calcining the crystals recovered in step c) to produce a calcined form of the molecular sieve.

8. Molecular sieve prepared according to the method of claim 1.

9. A catalyst comprising the molecular sieve of claim 8 and optionally a binder.

10. A hydrocarbon conversion process comprising the step of contacting a hydrocarbon feedstock with the catalyst as claimed in claim 9.

11. A hydrocarbon conversion process as claimed in claim 10 which is a dewaxing process or an aromatics alkylation process.

Citation Information

Patent Citations

  • Synthesis method of nanoscale MCM-49 (Multi Chip Module) molecular sieve

    CN103232044A

  • Manufacture of crystalline aluminosilicate

    JP1982077023A

  • Ammonia synthesis catalyst, production process therefor, and ammonia synthesis process

    JP2016059851A